Surgical Treatment of Erectile Dysfunction and Peyronie’s Disease Using Malleable Prosthesis - Yavuz, Ufuk; Ciftci, Seyfettin; Ustuner, Murat; Yilmaz, Hasan; Culha, Melih (Urology Journal, 2015)
Purpose: Peyronie's disease (PD) is a condition of middle aged men and frequently accompanied by erectile dysfunction (ED) which was attributed to penile deformity, vascular pathology and psychological components. The implantation of semi-rigid penile prosthesis allows for these patients to undergo a simple procedure aimed at correction both penile deformity and ED. The aim of this study was to investigate surgical and clinical outcomes and patient satisfaction rate at long term follow-up after semi-rigid penile prosthesis implantation (PPI) in men with PD and ED. Materials and Methods: A total of 66 patients with mean age of 49.2 (range, 30-76) years old underwent semi-rigid PPI between 1995 and 2006. Genesis (Coloplast®) was used for implantation in a standard manner by penoscrotal approach without using any graft and remodeling technique. In all patients, dilatation of corpora was performed without any difficulty and straightening of the penis was achieved. A retrospective review of clinical database and prospective telephone survey were conducted in all patients. Results: The mean follow-up time was 9.7 years (range, 6 to 17). There wasn't any clinical infection and complication during follow-up period. Fifty-nine patients were sexually active at the time of the interview. None of the patients reported residual curvature. The overall patient satisfaction was 91.5% (54 patients). Primary reasons for dissatisfaction were decreased penile length and prosthesis problems. Conclusion: Based on our results semi-rigid PPI is effective and easy procedure for treatment of men with PD and ED without any complication and with high patient satisfaction rate in long-term follow up period.